EVEN AS WE SPEAK : NEW ESSAYS 1993-2001 - James, Clive, 1939-2019, author 559780 (London : Picador, 2004)
Effervescent, energetic and insightful, Clive James is one of the twenty-first century's finest minds, and Even as we Speak one of its finest, funniest and sharpest volumes of essays.EVEN AS WE SPEAK is an illuminating and hilarious collection of essays from one of Picador's most beloved authors. Reflecting his comprehensive knowledge, wide-ranging interests and eclectic style, Clive James explores the rise and fall of various celebrities, discusses Australian poetry, considers the state of television today, questions the culpability of the ordinary German in the holocaust, and contemplates in a compellingly provocative and much-talked about piece the death of Diana.